Staphylococcus aureusosteoarticular infections in children: an 8‐year review of molecular microbiology, antibiotic resistance and clinical characteristics. Issue 12 (December 2018) - Bouras, Dimitrios; Doudoulakakis, Anastassios; Tsolia, Maria; Vaki, Ilia; Giormezis, Nikolaos; Petropoulou, Niki; Lebessi, Evangelia; Gennimata, Vasiliki; Tsakris, Athanasios; Spiliopoulou, Iris; Michos, Athanasios
Abstract : Purpose. : To investigate the clinical, phenotypic and genotypic characteristics of Staphylococcus aureus strains causing osteoarticular infections in a large paediatric series. Methodology. : Medical records of children who were hospitalized with the diagnosis of community‐associated S. aureus (CA‐SA) osteomyelitis and/or septic arthritis in the two major tertiary paediatric hospitals of Athens during an 8‐year period (2007‐2015) were reviewed, and S. aureus isolates were analysed regarding antimicrobial resistance, detection of pathogenicity genes and genotyping using SCC mec, agr typing, PFGE and MLST. Results. : During the study period, 123 children with CA‐SA osteoarticular infections were identified, and methicillin‐resistant S. aureus (MRSA) accounted for 44 of these (35.8 %). Children with MRSA infection had a significantly higher admission rate to the ICU (5.7 vs 0 %, P =0.04) and longer duration of hospitalization (21.6 vs 16.7 days, P =0.04). Sixty‐eight isolates [42 (methicillin‐sensitive S. aureus ) MSSA and 26 MRSA] were available for molecular analysis. All MRSA strains were mecA ‐positive and most carried the SCC mec IV cassette (23/26, 88 %) and belonged to the PFGE type C (24/26, 92.3 %), agr type 3 (24/26, 92.3 %) and the MLST ST80 clone (24/26, 92.3 %). In contrast, MSSA strains showed polyclonality by PFGE and agr typing. Regarding pathogenicity genes, MRSA vs MSSA isolates showed higher detection rates of PVL (96.2 vs 4.8 %, P <0.0001) and fib (80.8 vs 50 %, P =0.02). Conclusions. : In our study a considerable number of S. aureus osteoarticular infections were due to CA‐MRSA isolates, most of which belonged to the ST80 clone and had a higher incidence of specific virulence factors, entailing higher ICU admission rates and a longer duration of hospitalization.